Bioenhanced degradation of toluene by layer-by-layer self-assembled silica-based bio-microcapsules - Lin, Hongyang; Yang, Yang; Li, Yongxia; Feng, Xuedong; Li, Qiuhong; Niu, Xiaoyin; Ma, Yanfei; Liu, Aijv (Frontiers in Microbiology, 2023)
Abstract: Biotechnology is considered as a promising technology for the removal of toluene from the environment. However, the removal of toluene by free bacteria is greatly affected by environmental factors. In this study, bio-microcapsules were prepared by the layer-by-layer self-assembly (LBL) method using micron-sized monodisperse SiO2 microspheres as sacrificial templates with chitosan (CTS) and polylactic acid (PLA) as capsule wall materials, so as to enhance the resistance of bacteria to harsh environmental conditions. The successful preparation of LBL bio-microcapsules (LBMs) was confirmed by scanning electron microscope (SEM), transmission electron microscope (TEM). The biodegradation experiments of toluene and the determination of toluene degrading enzyme activity were also carried out under external adverse environmental conditions. The results showed that under harsh environmental conditions, the degradation rate of LBMs on toluene could basically reach more than 90% in 2 d, which was 1-4 times that of free bacteria. Flow cytometry analysis showed that LBL microcapsules could effectively reduce the death rate of the bacteria, which could protect the degrading bacteria. The results of the enzyme activity assay showed that the activities of toluene dioxygenase, catechol 1,2 dioxygenase, and catechol 2,3 dioxygenase of LBMs were significantly stronger than those of free bacteria under the same unfavorable external environmental conditions. In conclusion, the LBMs were more adaptable to the uncertain external environment, which provided a feasible bioremediation strategy for the treatment of organic contaminants in actual groundwater.